Efficacy of robotic transoral surgery (TORS) in the setting of oropharyngeal squamous cell carcinomas (OPSCC). An integrative literature review - Lauro Roberto de Azevedo Setton; Carlos Rodolfo de Góis; Daniel Vasconcelos D’Ávila; Roosevelt Almeida Rosário; Nelson Almeida Davila Melo; Scheilla Kristina Mesquita Salviano; Marta Dória dos Santos; Thiago Ribeiro Oliveira; Pedro Paulo Bittencourt Silva; Yuri Mark dos Santos Ribeiro; Antônio Roberto Ferreira Setton (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction: Transoral robotic surgery (TORS) demonstrates surprising oncological results from remarkable precision, maneuverability and expanded vision, but there is a gap in surgeons' knowledge regarding its effectiveness compared to other therapeutic methods.